Amperometric Detection of Nitrite Using Chitosan Protected Nickel Hexacyanoferrate Nanoparticles Modified Glassy Carbon Electrode - Jancy Sophia, S.; Devi, S.; P, K. (Asian Journal of Chemistry, 2013)
Zeolite type metal hexacyanoferrates have received much interest in recent days due to their unique properties such as electrocatalysis, biosensing and ion exchange characteristics. In the present study, we have synthesized chitosan protected nickel hexacyanoferrate nanoparticles by mixing an equimolar solution of NiCl2·5H2O and K3[Fe(CN)6] in presence of aqueous solution of chitosan. The resulting product was isolated and then characterized by FE-SEM, FT-IR and XRD techniques. Nafion is used as support to disperse nanoparticles for the modification of the electrode surface. The electrocatalytic oxidation of nitrite was investigated using chitosan protected nickel hexacyanoferrate nanoparticles (NiHCF NP) modified glassy carbon electrode (GCE) in phosphate buffer solution (PBS). A linear graph was obtained by plotting peak current against concentration of nitrite from 67.3 mM to 6.0 μM ranges. The detection limit was found to be 1.85 × 10-6 μM. The proposed method can be utilized for the electrochemical detection of nitrite in various environmental sources.